2015
DOI: 10.1148/radiol.14140796
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Pancreatic Cystic Lesions: Is There a Relationship with the Development of Pancreatic Adenocarcinoma and All-Cause Mortality?

Abstract: Purpose:To establish the effect of incidental pancreatic cysts found by using computed tomographic (CT) and magnetic resonance (MR) imaging on the incidence of pancreatic ductal adenocarcinoma and overall mortality in patients from an inner-city urban U.S. tertiary care medical center. Materials and Methods:Institutional review board granted approval for the study and waived the informed consent requirement. The study population comprised cyst and no-cyst cohorts drawn from all adults who underwent abdominal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 25 publications
5
40
0
4
Order By: Relevance
“…Additionally, several studies have demonstrated an association between pancreatic cysts and pancreatic ductal adenocarcinoma [7,[9][10][11][12]. Our results are in concordance with the literature, demonstrating 2.83 times higher odds of PDAC in patients with pancreatic cysts than in those without pancreatic cysts.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, several studies have demonstrated an association between pancreatic cysts and pancreatic ductal adenocarcinoma [7,[9][10][11][12]. Our results are in concordance with the literature, demonstrating 2.83 times higher odds of PDAC in patients with pancreatic cysts than in those without pancreatic cysts.…”
Section: Discussionsupporting
confidence: 92%
“…Chernyak et al previously showed in a large retrospective cohort study that the majority of pancreatic adenocarcinomas that developed in patients with pre-existing pancreatic cysts occurred in a location different from the original cyst [7]. In addition, Bartsch et al demonstrated that in patients with familial pancreatic cancer, small intraductal papillary mucinous neoplasms are associated with the presence of high-grade pancreatic intraepithelial neoplasia (a precursor to adenocarcinoma) elsewhere in the pancreas [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding concurs with the results of a recent large study of 2034 patients with pancreatic cysts and 6018 patients without pancreatic cysts in whom the presence of at least 1 pancreatic cystic lesion resulted in a 3-fold higher probability of pancreatic adenocarcinoma. 12 A retrospective cohort study of adult patients with pancreatic cysts evident on medical record review found that patients could be stratified into low-, intermediate-, and high-risk categories on the basis of 4 cross-sectional imaging features: size, pancreatic duct dilation, septations with calcifications, and growth. 13 Patients with cysts 2 cm or less with no other suspicious imaging features have a very low probability of malignancy developing (≤ 0.6%), whereas these authors suggest that patients with cysts sized 1 cm to 3 cm that also have at least 1 suspicious imaging characteristic deserve close surveillance.…”
Section: Discussionmentioning
confidence: 99%